The effect of different Intensities of circuit resistance training on plasma neuregulin and leptin concentrations in young men - Abbas Ghanbari-Niaki; najmeh rezaei nezhad; rostam Alizadeh (Shahid Beheshti University, 2019)
Purpose: The purpose of this study was to investigate the effect of different Intensities of circuit resistance training on plasma neuregulin and leptin concentrations in young men.Methods: Forty-five healthy young men [21.55± 0.17 years old; height= 175.42± 0.88 cm, weight= 73.10±1.63 Kg] were randomly divided into 5 groups (control, 20, 40, 60 and 80% 1RM). Men of training groups performed circuit resistance training 4 times a week with given intensities for 6 weeks. The blood sampling was conducted to determine the levels of neuregulin-1, leptin, insulin, and glucose before, and after 6 weeks. Data were analyzed using the analysis of covariance and paired T-test.Results: The plasma neuregulin-1 (P= 0.0001), leptin (P= 0.009), and insulin (P=0.013) levels were significantly increased in the training groups compared with the control group while there were no significant differences between the glucose (P=0.27) level of groups.Conclusion: The results showed circular resistance training plays a significant role in promoting the performance of NRG-1 and leptin.